(untitled) (Genitri: Jurnal Pengabdian Masyarakat Bidang Kesehatan, 2025)
The objectives of the Sustainable Development Goals (SDGs) is to improve maternal and child health, including the health of adolescents and pregnant women. Villages must be strengthened in health independence, especially villages that care about adolescents and pregnant women. Cadre skills need to be continuously improved both in health services and prevention of anemia and its impact on stunting cases. The solution offered is the Establishment of a Village that Cares About Adolescents and Pregnant Women "SIJAMIL" Based on Local Wisdom as an effort to empower and independence in maternal and child health and early prevention of stunting in Dajan Peken Tabanan Village. Increasing adolescents and pregnant women to come to the integrated health post (posyandu). Training cadres to utilize local food sources rich in iron nutrition. Assistance to cadres and evaluation of the implementation of health services for adolescents and pregnant women in Dajan Peken Tabanan Village. Activities are carried out using socialization, training and practice methods, mentoring, monitoring and evaluation. The results of this activity are an increase in knowledge from 63% less to 88% good. Improvement of cadre skills in implementing health services, especially monitoring signs of anemia in adolescents, signs of danger in pregnancy. Efforts to utilize local food sources to make nutritious food for teenagers and pregnant women.